Phytochemical Screening and Antibacterial Activity of Ethanolic Extracts from Delonix regia Against Laboratory Strains of Diarrheal Bacteria - Yeyen Susana Senge; Irfan Mustafa; Anna Safitri (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
The present study evaluates the antibacterial efficacy of ethanolic extracts from Delonix regia leaves against diarrhea-inducing bacteria Escherichia coli and Salmonella typhimurium. Preliminary phytochemical screening revealed that D. regia leaves comprise flavonoids, alkaloids, saponins, tannins, phenolics, and terpenoids. Fourier Transform Infrared Spectroscopy (FTIR) analysis identified various functional groups in the D. regia leaf extract, including O-H, C-H, C=O, C=C, C-C, C-O, and C-O-C. Liquid Chromatography-Mass Spectrometry/Mass Spectrometry (LC-MS/MS) analysis further confirmed the presence of 16 distinct compounds comprising amino acids, alkaloids, phenolics, flavonoids, terpenoids, anthraquinones, n-acyl pyrrolidines, and fatty acids. The disc diffusion method (Kirby-Bauer) was employed for the antibacterial tests. The extracts of D. regia leaves at concentrations of 25%, 50%, 75%, and 100% generated inhibition zones measuring 5.26 mm, 6.37 mm, 7.27 mm, and 10.18 mm against E. coli, and 5.05 mm, 7.01 mm, 8.77 mm, and 10.04 mm against S. typhimurium, respectively. The commercial antibiotic ciprofloxacin (a positive control) produced inhibition zones of 30.02 mm for E. coli and 28 mm for S. typhimurium. The negative control, consisting of 10% ethanol, showed no inhibitory effect on bacterial growth. These findings indicate that the ethanolic extract of D. regia leaves possesses antibacterial properties against E. coli and S. typhimurium. It is likely that secondary metabolite compounds, such as flavonoids and phenolics, contribute significantly to the observed antibacterial activity